2017
DOI: 10.1371/journal.pone.0178077
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas emissions from dung pats vary with dung beetle species and with assemblage composition

Abstract: Cattle farming is a major source of greenhouse gases (GHGs). Recent research suggests that GHG fluxes from dung pats could be affected by biotic interactions involving dung beetles. Whether and how these effects vary among beetle species and with assemblage composition is yet to be established. To examine the link between GHGs and different dung beetle species assemblages, we used a closed chamber system to measure fluxes of carbon dioxide (CO2), methane (CH4) and nitrous oxide (N2O) from cattle dung pats. Tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 50 publications
2
71
1
Order By: Relevance
“…Dung beetles (Coleoptera: Geotrupidae, Scarabaeidae, Aphodiidae) are model organisms that are frequently used to test relations between biodiversity and ecosystem functioning. Both mesocosm and field experiments showed that different species contribute highly unevenly to ecosystem functioning and that trait-based trade-offs in space and time regarding ecosystem functions are likely (Larsen et al, 2005;Slade et al, 2007;Rosenlew & Roslin, 2008;Slade et al, 2011;Manning et al, 2016;Piccini et al, 2017). One of the basic functions provided by dung beetles is dung removal, to which the other functions are highly connected (Holter, 1979;Slade et al, 2007;Nichols et al, 2008;Nervo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Dung beetles (Coleoptera: Geotrupidae, Scarabaeidae, Aphodiidae) are model organisms that are frequently used to test relations between biodiversity and ecosystem functioning. Both mesocosm and field experiments showed that different species contribute highly unevenly to ecosystem functioning and that trait-based trade-offs in space and time regarding ecosystem functions are likely (Larsen et al, 2005;Slade et al, 2007;Rosenlew & Roslin, 2008;Slade et al, 2011;Manning et al, 2016;Piccini et al, 2017). One of the basic functions provided by dung beetles is dung removal, to which the other functions are highly connected (Holter, 1979;Slade et al, 2007;Nichols et al, 2008;Nervo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the total biomasses in the treatments between the two species were comparable, the results in terms of ecosystem functioning are very different: higher efficiency of C. lunaris species in comparison with O. illyricus . This is in agreement with previous studies that have shown that, even at the same total biomass, larger beetles are more effective than smaller ones (Kaartinen et al ., ; Nervo et al ., ; Piccini et al ., ). Moreover, based on the results from previous work on dung removal by monospecific (Tixier et al ., ) and mixed (Yamada et al ., ) assemblages of dung beetle species at high densities (Giller & Doube, ), we hypothesised that beetle abundance, biomass, and species identity would have a positive effect on dung removal across treatments.…”
Section: Discussionmentioning
confidence: 97%
“…Although limited in factors such as scale/replication, time frame, geographic range and dung beetle species, our results add to the literature showing that there are important ecosystem service benefits from dung beetles (e.g. Slade et al ., ; Beynon et al ., ; Manning et al ., ; Manning et al ., ; Piccini et al ., ). These findings are relevant both to agricultural systems where native dung beetle faunas are at risk from intensification of agriculture (Hutton & Giller, ) or systems where there are naturally impoverished dung beetle faunas, with active release programmes aiming to increase species richness (Edwards, ; Forgie et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…If an entire country has a naturally impoverished pastoral dung beetle fauna, then many species of dung beetle may require to be introduced to achieve improvements in ecosystem services over seasons and in pastures that will vary in factors such as farming types, soils, or climates (Tyndale-Biscoe, 1994;Edwards, 2009). Furthermore, evidence suggests that more diverse dung beetle communities can provide better benefits to ecosystem services than comparatively species-poor communities, but that species composition effects can be complex and warrant further study (Slade et al, 2007;Beynon et al, 2015;Manning et al, 2016;Manning et al, 2017;Piccini et al, 2017;Slade et al, 2017).…”
Section: Conclusion and Caveatsmentioning
confidence: 99%